2018
DOI: 10.3390/f9070414
|View full text |Cite
|
Sign up to set email alerts
|

Recent Drought-Induced Vitality Decline of Black Pine (Pinus nigra Arn.) in South-West Hungary—Is This Drought-Resistant Species under Threat by Climate Change?

Abstract: This paper analyses the recent recurring dieback and growth decline of Black pine (P. nigra Arn. var austriaca) in the Keszthely mountains of south-west Hungary, and their relations to water deficits due to droughts. These relations were studied in five stands with low soil water storage capacity for the period 1981-2016. The vitality was assessed using 60 tree-ring samples and changes in remotely sensed vegetation activity indices, i.e., the normalized difference vegetation index (NDVI) and the normalized dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 64 publications
2
20
0
Order By: Relevance
“…Our projections suggest a strong shrinkage of the species' habitat suitability, which, under the extreme SSP5-8.5 scenario, can reach up to 75% of its current extent (Table 2). Ecophysiological studies have found that P. nigra is relatively vulnerable to drought [63,64], with growth declines and diebacks reported, particularly in southern populations [65][66][67]. Empirical models suggest that under climate change, the growth of P. nigra in the Iberian Peninsula is expected to decrease, except for northern and productive areas [68,69].…”
Section: Discussionmentioning
confidence: 99%
“…Our projections suggest a strong shrinkage of the species' habitat suitability, which, under the extreme SSP5-8.5 scenario, can reach up to 75% of its current extent (Table 2). Ecophysiological studies have found that P. nigra is relatively vulnerable to drought [63,64], with growth declines and diebacks reported, particularly in southern populations [65][66][67]. Empirical models suggest that under climate change, the growth of P. nigra in the Iberian Peninsula is expected to decrease, except for northern and productive areas [68,69].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of cases averaged growth of successive dry years [13,23,[57][58][59][60][61]. However, a few studies used the value of the last year of the drought event [62,63], and some studies did not explain how they dealt with this issue [64][65][66]. Since these two approaches (average vs. last year of drought period) are likely to yield different results, we recommend that the results obtained are at least compared for the different approaches when dealing with successive dry years.…”
Section: Consideration Of Climatic Conditions In the Pre-and Post-dromentioning
confidence: 99%
“…Compared to annual allowable cut, in the peak year of salvation felling, a three times higher volume was removed and second-order trees and shrubs took over [88]. Móricz et al [107] recently published further details on Austrian (black) pine mortality. introduction of better adapted non-native species to future climatic conditions, have especially raised public controversy.…”
Section: Typifying Of Forest Sites and Their Yield Potential (A Bimentioning
confidence: 99%